Reproduction Identity Mechanism at Pasek Community in Mataram City, West Nusa Tenggara - I Wayan Ardhi Wirawan (Humaniora, 2011)
Reproduction identity at Pasek community in Mataram indicated by re-emphasizing symbolic power genealogical identity which had been built by their ancestor. Those phenomenon is patterned throught personal genealogical identification, representation of ancestor’s identity at Pasek clan in socio-religious space, identity articulation in priesthood symbol construction, and restructuring established cultural in Hindu religiousity practice. Socio-religious movement is actuated by Pasek community closely related with their struggle to achieve symbolic power in practicing Hindus religiousity.